Study Protocol of the Ten Years Up Project: Mapping the Development of Self-Regulation Strategies in Young Adults Over Time - Gillebaart, Marleen; Brummelman, Jantina; de Ridder, Denise (Frontiers in Psychology, 2021)
Research thus far has not systematically addressed the development of self-regulation strategies during young adulthood, but instead has focused on the predictive value of childhood self-regulation competence for outcomes later in life. The present study protocol describes the Ten Years Up (10YUP) project, a longitudinal cohort of young adults who will be followed for ten years. By adopting a dynamic approach, we aim to examine how the nature and frequency of self-regulation strategies develop over time, document to what extent the use of strategies is affected by contextual and personal factors, and determine how these strategies affect health and wellbeing over the course of ten years. The 10YUP project employs a prospective longitudinal design to map the development of self-regulation strategies over time. A sample of 3000 participants will be recruited by random selection from the general population of 16-year olds to retain a final sample of 1000 participants after ten years (accounting for an estimated drop-out rate of 10% each year). A mobile app will be used to collect data every three months. Self-regulation strategies will be assessed by means of the Goal Setting and Striving Inventory that asks participants to list their personal goals and then choose their most important goal to answer items about goal perception and strategy use. The resulting composite self-regulation index will be related to a wide range of contextual and personal factors that may act as either antecedents or consequences of self-regulation, depending on their specific time of assessment (either prior to or following self-regulation assessment) by means of cross-lagged panel analyses and other analyses allowing for establishing causal relationships over time. The 10YUP project is likely to generate novel insights into the development of self-regulation in young adulthood, how this development is affected by personal and contextual factors, and how these in turn may be influenced by how young people self-regulate – which is important for public policies aimed at guiding young people’s choices and how they affect their health and wellbeing.